(3MGTjI Ydi GdQSGdI GdMSjfjI aj BOGH GdHMKs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; jG ef habfG dhXGFa GdHMK hjG cdeI eTJQcI Hjf GdCMhGd GdKdGKI adG JMJGL Edi JhLjg GdYdGeI hGdeQGO HgG ZGjI eYfGgG hgj GdELGHI, hGdJhajb dZI LYd GdCSHGH ehGabI fMh GdeSHH hGUWdGMG Ndb GdbOQI Ydi GdWGYI hGdHMK dZI GdJaJjT hGUWdGMG GKHGJ GdeOYj HGdOdjd s
(3BNQgG (B:s
(3hJGSYgG Cfg dG jMSH Cf NUeg MbjQ VYja dFdG jDOj GSJMbGQg Edi UOhQ GdcdGe GdSNja ajchf eZdhHG ddNUe GdVYja HGdEaMGe eY Cf gPG CTfY hLhOg GdGdRGe hYdi Gddg GdJhcd hHg GdGYJUGes
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdMhGTj h GdJYdjbGJ (B:s
(3JYdjbGJs
Keywords: (3GdadSaI hGdefWbs